One Pot Synthetic Method of New Keto Diphenyl Selenide Compounds - Youcef Mechehoud; F. Benayache; S. Benayache; P. Mosset (E-Journal of Chemistry)
A series of hitherto unreported mono- and di-keto diphenyl selenides have been efficiently synthesized in high yields by treatment of diphenyl selenide (1) with appropriately substituted acyl chloride using anhydrous aluminum chloride as catalyst and methylene chloride as solvent. The structures of the synthesized compounds have been confirmed by elemental and spectral analysis.